Inter‐rater reliability of the Clinical Frailty Scale by staff members in a Swedish emergency department setting. (19th October 2022) - Hörlin, Erika; Munir Ehrlington, Samia; Henricson, Joakim; John, Rani Toll; Wilhelms, Daniel
Abstract: Introduction: As frailty among the elderly is receiving increasing attention in emergency departments (EDs) around the world, the use of frailty assessment tools is growing. An often used such tool is the Clinical Frailty Scale (CFS), whose inter‐rater reliability has been sparingly investigated in ED settings. No inter‐rater reliability study regarding CFS has previously been performed within the Scandinavian ED context. The primary aim of this study was to evaluate the inter‐rater reliability of the CFS in a Swedish ED setting. Methods: This was a prospective observational study conducted at three Swedish EDs. Patients ≥65 years were independently assessed with CFS by their responsible physician, registered nurse, and assistant nurse. Demographic information for each assessor was collected, along with frailty status (frail/not frail) on the basis of clinical judgment. Inter‐rater reliability was calculated using intraclass correlation coefficient (ICC), whereas agreement of frailty assessed by CFS (dichotomized between frail/not frail, cutoff at ≥5 points) versus solely by clinical judgment was calculated by using cross‐tabulation. Results: One‐hundred patients were included. We found inter‐rater reliability to be moderate to good (ICC 0.78, 95% confidence interval [CI] 0.72–0.84), regardless of whether the care team included an emergency physician (ICC 0.74, 95% CI 0.62–0.83) or an intern/resident from another specialty (ICC 0.83, 95% CI 0.74–0.89). The agreement of clinically judged frailty compared to frailty according to CFS was 84%. In the opposing cases, staff tended to assess patients as frail to a higher extent using clinical judgment than by applying CFS on the same patient. Conclusions: The CFS appears to have a moderate to good inter‐rater reliability when used in a clinical ED setting. When guiding clinical decisions, we advise that the CFS score should be discussed within the team. Further research needs to be performed on the accuracy of clinical judgment to identify frailty in ED patients.